Total penectomy as treatment option for solitary penile metastasis in hormone sensitive metastatic prostate cancer (mHSPC): Case report with surgical technique - M. Vukovic; M. Albijanic; N. Radovic (Urology Case Reports)
We present a case of a 66-year-old man with a three-year history of Gleason 10 prostate cancer (PCa), who presented with penile pain, erythema, and induration of the penile shaft. His cancer was treated with androgen deprivation therapy (ADT), radiotherapy, and apalutamide, resulting in PSA reduction; however, a solitary penile lesion persisted, necessitating radical penectomy. At 12 months post-surgery, PSA levels and magnetic resonance imaging findings remained stable, with no signs of metastasis. This case highlights the viability of radical penectomy for solitary penile metastasis in hormone-sensitive metastatic prostate cancer (mHSPC), with potential benefits for symptom control and survival.